Strategi Kolaborasi Hexehelix Dalam Membangun Pariwisata Karawang - Neni Sumarni; Ihsan Nasihin; Vidya Arisandi; Yeni Fajrin (Pusat Riset dan Inovasi Nasional, 2025)
Karawang's tourism potential is enormous and offers a wide variety of tourism options. Known as an industrial city and a rice barn, Karawang, despite its significant tourism potential, has been unable to attract tourists, both domestic and international. Therefore, an appropriate collaborative strategy is needed to develop Karawang tourism. The purpose of this study is to develop a Hexahelix concept and strategy for Karawang tourism, ensuring its integration and optimal development. The research method used is descriptive qualitative. The results indicate the absence of a hexahelix concept for Karawang tourism and the lack of integration between the interconnected elements of the helix within Karawang tourism. The Hexahelix strategy, with its six elements, is necessary for integrated collaboration for Karawang tourism, so that Karawang tourism development can proceed optimally. With the synergy of these six elements, tourism development will be more sustainable, inclusive, and have a real impact on regional welfare. The Hexahelix concept for Karawang tourism is to build synergistic collaboration among the six elements (government, academics, businesses, communities, media, and investors) by placing the community at the core, supported by academic research, government regulations, private investment, media promotion, and sustainable funding.